Pregnancy rates and luteal phase characteristics of bovine embryo recipients treated with flunixin meglumine - Cardoso, R. C. [UNESP]; Codognoto, V. M. [UNESP]; Lainetti, P. F. [UNESP]; Yamada, P. H. [UNESP]; Rizzoto, G.; Salgado, L. C. [UNESP]; Araújo, M. S. [UNESP]; Vieira, A. F. [UNESP]; Marques, N. F.S. [UNESP]; Oba, E. [UNESP] (My University, 2020)
The aim of this study was to evaluate the effects of flunixin meglumine administration on pregnancy rates and luteal phase characteristics in bovine embryo recipients at the moment of embryo transfer. In experiment 1, in vitro produced embryos were transferred to 184 females divided as control and treated group (recipients treated with 1.1mg/kg flunixin meglumine). In experiment 2, 22 females were divided as control group; group 2 (animals submitted to a reproductive tract manipulation similar to an embryo transfer on the 7th day after estrous); and group 3 (females submitted to a manipulation and treatment with 1.1mg/kg flunixin meglumine). In experiment 1 no difference was observed between control and treated groups (40.2% and 44.6%, respectively) for pregnancy rates. In experiment 2 no difference was observed on the length of luteal phase between groups, however, animals in group 2 presented lower plasma progesterone concentrations than the control group and group 3. Therefore, we concluded that although the administration of flunixin meglumine at the moment of embryo transfer inhibited the reduction plasma progesterone concentrations, it was not effective in increasing pregnancy rates of bovine recipients.
Keywords: Bos taurus; Corpus luteum; Flunixin meglumine; Progesterone